Stressors and Support Experienced by Active Duty U.S. Navy Sailors at Sea - Hurtado, Lauren M; Harrison, Elizabeth M; Englert, Robyn M; Perez, Vanessa G; Thomsen, Cynthia J; Schmied, Emily A (Military medicine, 2025)
High occupational stress is generally associated with poorer mental health and reduced performance in military personnel, whereas access to support resources is associated with positive outcomes. However, little research has examined the unique stressors and supports experienced by sailors on ships while underway at sea. The objectives of this study were to (1) identify sailors' underway stressors and supports and (2) examine how these differ as a function of demographic and operational factors. Active duty U.S. Navy sailors reporting an underway period lasting at least 30 days within the last 5 years (n = 441; 74.7% male, 90% enlisted) completed an anonymous retrospective survey. Sailors completed measures assessing underway stressors (25 items) and supports (9 items), as well as demographic, military, and operational characteristics (sex, rank, ship type, and underway duration). The study protocol was approved by the Naval Health Research Center Institutional Review Board in compliance with all applicable federal regulations governing the protection of human subjects. Overall, the stressors rated as most problematic were exposure to loud noises, inability to rest when needed, unavailability of quality mental and physical health care, and not having enough people to complete the mission. Sailors perceived the most available supports to be opportunities to socialize, safety while performing duties, and finding ways to relieve stress. Female and enlisted personnel, relative to male and officer personnel, respectively, generally perceived stressors as more problematic and support resources as less available. Nearly half of the sample (48.3%) reported that services and programs to help them deal with stress while at sea were inadequate. Sailors experience many stressors while underway. Increasing the resources available to underway sailors may be warranted, especially for female and enlisted personnel. Additional research is necessary to develop targeted interventions and resources. Possible recommendations include noise mitigation, berthing area improvements, sleep and/or scheduling interventions, improved access to mental and physical health care, and interventions to reduce the stigma associated with seeking mental health care.